Pengaruh Etos Kerja, Komunikasi Dan Motivasi Kerja Terhadap Disiplin Kerja Karyawan PT XYZ - Mita Rahmadewi; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to examine the influence of work ethic, communication and work motivation on employee work discipline. Work discipline is an important factor in increasing organizational productivity and performance. Factors such as work ethic, communication and work motivation have a significant role in shaping the level of employee work discipline in the work environment. This research uses a quantitative approach by collecting data through questionnaires distributed to 100 employee respondents from various backgrounds and levels of position. The collected data was analyzed using statistical methods such as regression to assess the relationship between the independent variables (work ethic, communication and work motivation) and the dependent variable (work discipline). The results of the analysis show that there is a positive and significant influence of work ethic, communication and work motivation on employee work discipline. The SmartPLS 4 application was also used in this research to assist in the analysis of the data obtained. The findings of this research provide an important contribution to human resource management and organizational development.